DARI SOCRATES KE CHATGPT: TRANSFORMASI ETIKA KEILMUAN DI ERA KECERDASAN BUATAN GENERATIF DAN IMPLIKASINYA BAGI MAHASISWA PENDIDIKAN TINGGI (2021–2025) - Bayu Kurniawan; Yuliati Hotifah; Sofyan Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The emergence of generative AI, particularly ChatGPT since late 2022, has triggered structural disruption to academic ethics in higher education. This study maps the transformations in academic ethics during the generative AI era and their implications for students, employing an analytical framework integrating educational psychology and guidance and counseling. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines and the PICOC framework via the Scopus database. From an initial pool of 865 articles, 28 met the inclusion criteria. Findings reveal five convergent dimensions of transformation: reconceptualization of plagiarism (AI-giarism), normalization of AI-assisted academic misconduct, erosion of epistemic ownership (digital centaur authorship), stratification of students' moral reasoning, and structural asymmetry between technology adoption and institutional governance. Analysis through the lenses of Kohlberg's moral development theory, self-regulated learning, and cognitive dissonance demonstrates that student behavior toward AI is shaped by the interplay of moral reasoning, self-regulation, and cognitive tension. Adequate institutional responses require the integration of policy, pedagogy, and psychological support through strengthened guidance and counseling services to reconstruct the epistemic culture of higher education in the AI era.